Antioxidant Activity, Toxicity Test and Antimicrobal Test of Streptococcus mutans and Candida albicans Extract Of Ultrasound Assisted Extraction of Java Chili (Piper retrofactum Vahl.) Leaves - Djarot, Prasetyorini; Pertiwi, Anindita Aulya; Yulianita; Dewi, Fitria; Safira, Nurul; Firda, Varisa Yulia (Corespub, 2025)
P. retrofractum leaves are widely cultivated by the community to be used as traditional medicine, this is because of its secondary metabolite content which has several bioactive components such as steroids, flavonoids, alkaloids, saponins, tannins and has pyhtol and piperine compounds as dominant compounds that have antimicrobial potential. This study aims to determine flavonoid content, antioxidant activity and cytotoxic test of P. retrofractum leaf extract. The extraction method used was Ultrasound Assisted Extraction (UAE) with 3 solvents of different polarity, namely n-Hexan, ethyl acetate and 70% ethanol. Determination of flavonoid content using UV-Vis spectrophotometric method, determination of antioxidant activity using DPPH method and cytotoxic activity test using Brine Shrimp Lethality Test (BSLT) method. Antibacterial activity test was conducted by measuring the Minimum Inhibitory Concentration (KHM) and Diameter of Inhibitory Area (DDH). KHM test was done by agar dilution method, DDH test by disc paper diffusion method. The results of the extraction of P retrofractum leaves produce the highest yield is ethanol extract which is 9.92%. The result of determining the highest flavanoid content is 70% ethanol extract at 1.2702%. The strongest antioxidant activity is 70% ethanol extract with an IC 50value of 40.7475 ppm with a very strong category. The results of the cytotoxic test showed that the three types of extracts were toxic because they had LC50 less than 1000 µg/mL. The best KHM result for S. mutans is 10% n-hexane extract and 10% ethyl acetate and for Candida albicans is 5% n-hexane extract. The best DDH of S. mutans was 20% n-hexane extract with a value of 17.37 mm approaching Susceptible (Intermedate) and the best DDH of Candida albicans was obtained by 20% n-Hexan extract with an average DDH of 17.12 mm approaching Susceptible (Intermedate).